Previous Intestinal Resection Is Associated with Postoperative Complications in Crohn’s Disease: A Cohort Study - Yantao Duan; Yifan Liu; Yousheng Li (Gastroenterology Research and Practice)
Background. To assess the influence of a previous intestinal resection on postoperative complications for Crohn’s disease (CD). Methods. Data on patients with CD undergoing surgery in our department from January 2016 through December 2019 were retrospectively reviewed. Information collected included demographic details, surgical data, and postoperative outcome. A cross-sectional study design was employed. Associations between postoperative complications and preoperative clinical indicators were further analyzed. Results. Of the 129 patients with CD studied, 62 patients (48.06%) underwent previous resection. These patients were more likely to be older (P=0.031), have longer disease duration (P=0.025), use less 5-aminosalicylic acid/sulfasalazine preoperatively (P=0.013), have lower body mass index (P=0.003), and have a higher American Society of Anesthesiologists (ASA) Physical Status Classification System score (P=0.043). Patients who had previous surgery had a longer duration of operation (P=0.003), greater estimated blood loss (P=0.001), and longer hospital stay (P<0.001) and were more inclined to develop postoperative complications (P=0.047), particularly anastomotic leak (P=0.021) and severe (Clavien–Dindo grade III/IV) complications (P=0.038). After multivariate analysis, previous intestinal resection (P=0.019), preoperative use of steroids (P=0.026), and ASA score of more than II (P<0.001) were determined to be the independent prognostic risk factors for postoperative complications. During the 30-day follow-up period, there was no postoperative mortality or readmission. Conclusions. Previous intestinal resection in patients with CD is an independent predictor of overall postoperative complications.